Ravencliffe - Goodman, Carol (Viking, an imprint of Penguin Group (USA), 2014)
Seventeen-year-old Ava Hall continues to learn more about herself and her heritage through her work in a New York City settlement house as well as through her social obligations with the Blythewood girls.